Bioavailability of crude protein and lipid from biofloc meals produced in an activated sludge system for white shrimp, Litopenaeus vannamei - Sabry Neto, Hassan (2015)
The present study compared the bioavailability of crude protein and lipid from biofloc meals generated with an activated sludge system using two water sources: wastewater from shrimp experimental culture (BFL-W) and, artificially, using clean seawater (BFL-C). The sludge system operated by chemical and organic fertilization three times per week. Sampling of bioflocs occurred every two days during 81 days. To evaluate digestibility, each type of biofloc meal was incorporated into a reference diet (REF) at 300 g/kg. Another diet acted as a negative control (NEG) by using fish waste meal. The apparent digestibility of bioflocs was estimated by the indirect method using chromic oxide (Cr2O3) as the inert marker at 10 g/kg of the diet. Juvenile L. vannamei of 5.09±0.79 g (n = 440) were stocked at 10 shrimp/tank in 44 tanks of 61 L each that operated under a water recirculating regime. Biofloc meals contained a high ash content (591.0-649.2 g/kg) combined with a low crude protein content (95.9-137.3 g/kg). After 26 days, shrimp achieved a final survival of 93.2±0.8% and a biomass gain of 37.1±1.8 g/tank. Final shrimp body weight ranged from 9.01±0.15 to 9.45±0.13 g. The apparent digestibility coefficient (ADC) of crude protein in the biofloc produced from BFL-W, BFL-C and fish waste meal (NEG) reached 26.0, 25.7, and 64.1%, respectively. Similarly, the lipid ADC was 78.9, 67.9, and 85.8%, respectively. This study indicated that biofloc meals had a low protein availability for L. vannamei. However, although low levels of lipid were present, it proved to be available for the species. The dietary inclusion of biofloc meal appears to have a growth-promoting effect on shrimp, which may be associated with trace minerals, or other nutrients not identified in this study.